Appropriateness of hysterectomy for various indications - Bajpai, Surabhi A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study appropriateness of hysterectomy for various indications by evaluating the referred cases for hysterectomy as per standard norms and calculating number of hysterectomies which were not indicated. Methods: A prospective study consist of analysis of 110 cases which were advised hysterectomies in different hospitals due to various indications and number of cases who were managed conservatively in these 110 cases and did not required hysterectomy ultimately. Results: There was significant difference in number of cases who were advised hysterectomies and number of cases who actually needed a hysterectomy. Most of cases were advised hysterectomy just on the basis of patient’s complaints with no consideration to age, parity and without proper evaluation as per standard norms. Conclusions: It was found that only 27.27% of cases who were advised hysterectomies actually needed hysterectomy for indications like symptomatic fibroid, severe dysplasia, resistant cases of AUB and intractable pain due to adenomyosis and 72.73% of cases were managed conservatively and indications for which hysterectomy was advised in such cases were inappropriate.